Malaysia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2018)
This Selected Issues Paper presents an overview of the Malaysian labor market. Malaysia's economy and its labor market have undergone significant shifts in the last three decades. The labor market is now more urban and has a higher share of female workers and workers with tertiary education. Employment has kept pace with labor supply, keeping the unemployment rate stable for more than a decade. Meanwhile, reliance on noncitizen workers has also increased against the backdrop of slower growth in citizen population. Continuing with its economic transformation, Malaysia aspires to achieve high-income status, with a labor market that is ready for the economy of the future: a market that can support more female workers, more skilled jobs, and a higher labor productivity growth.